2016
DOI: 10.1002/ceas.12029
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi Study and Initial Validation of Counselor Supervision Competencies

Abstract: The authors addressed the lack of supervision training standards for doctoral counseling graduates by developing and validating an initial list of supervision competencies. They used content analysis, Delphi polling, and content validity methods to generate a list, vetted by 2 different panels of supervision experts, of 33 competencies grouped into 5 categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…This study helps address the gap in the literature related to preparing counselor education doctoral students to teach. The broad categories of teaching competency (i.e., knowledge, skills, professional behaviors, and dispositions) identified in this study have some similarities with other studies exploring and assessing areas of competency within the counseling profession, including counseling competencies (Lambie, Mullen, Swank, & Blount, 2018; Swank et al, 2012), research competencies (Swank & Lambie, 2016; Wester & Borders, 2014), and supervision competencies (Neuer Colburn et al, 2016).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This study helps address the gap in the literature related to preparing counselor education doctoral students to teach. The broad categories of teaching competency (i.e., knowledge, skills, professional behaviors, and dispositions) identified in this study have some similarities with other studies exploring and assessing areas of competency within the counseling profession, including counseling competencies (Lambie, Mullen, Swank, & Blount, 2018; Swank et al, 2012), research competencies (Swank & Lambie, 2016; Wester & Borders, 2014), and supervision competencies (Neuer Colburn et al, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Although defining the criteria for an expert is challenging within this methodology (Strear et al, 2018), Baker, Lovell, and Harris (2006) reported themes present in research regarding the definition of an expert that included knowledge, experience, and influence on policy. In the current study, we identified experts by using the themes presented by Baker et al, as well as protocol used in recent Delphi studies focused on areas of competency within counselor education (e.g., Neuer Colburn, Grothaus, Hays, & Milliken, 2016 [supervision competencies]; Wester & Borders, 2014 [research competencies]). Participants were required to have a doctoral degree in counselor education and be employed as a counselor educator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a 22% response rate is typical for online surveys (Nulty, 2008), and the sample size provided enough statistical power to conduct the analyses given the large amount of variance explained in each of the models. Second, the sample primarily included faculty who identified as female and White, but these demographics are representative of most studies within counselor education (e.g., Brown‐Rice & Furr, 2015; Neuer Colburn, Grothaus, Hays, & Milliken, 2016). Third, given the lack of demographic information on nonrespondents, we were unable to explore whether they differed from respondents on any demographic information.…”
Section: Discussionmentioning
confidence: 99%
“…There are subtle differences from those dynamics and processes in both individual and group supervision, and doctoral student supervisees are typically uncertain of their role in triadic supervision (Borders et al, ). The emerging work on establishing supervision competencies for doctoral program graduates should also be considered (Colburn, Grothaus, Hays, & Milliken, ).…”
Section: Discussionmentioning
confidence: 99%